Pengaruh GA3 dan Beberapa Jenis Larutan Kimia Terhadap Bunga dan Karakter Morfologis Tetua Padi Hibrida - Yuni Widyastuti; Sri Wahyuni; Indria Wahyu Mulsanti (Jurnal Ilmu Pertanian Indonesia, 2016)
The aim of the present study is to optimize the dose of GA3 and substitution chemicals that affect on floral and morphological traits of parental lines for hybrid rice seed production. The experiment was conducted at glass house on field station Sukamandi, Indonesian Center for Rice Research, during April-August 2010. The experimental material comprising both the parental lines of hybrid Hipa 7 i.e. IR58025A and IR40750 were treated with 10 treatments of different kind of GA3, chemicals, and one untreated check was grown in randomized block design with three replications. The results indicated that a liquid GA3 60 ppm, urea 2%, phosphate 1%, and glycine 40 ppm could influence some of the characters favoring outcrossing i.e stigma exertion, panicle exertion, anther and filament length. These chemical (urea 2%, phosphate 1%, and glycine 40 ppm) showed the possibility of the economizing cost of seed production and substitute of GA3